Haematological Parameters of Neonate Camels (Camelus dromedarius) During the First Week of Life - Elkhair, Nawal Mohamed; Elmgboul, Wallieldin Elsadig (Journal of Veterinary Medicine and Animal Production, 2021)
Haematological parameters were studied in 22 neonate dromedary camels during their first week of life. Blood samples were collected from the jugular vein and for the determination of blood haemoglobin concentration (Hb), blood haematocrit (HCT), total red blood cells count (RBCs), total and differential leukocytes count. The significantly (P<0.05) higher mean value for blood- [Hb] of 12.9±0.6 g/dl was observed in neonate camels on the 1st day of life. On the 5th day of life, neonate camels showed a significant (P<0.05) higher percentage of HCT (31%) compared to the other days. Erythrocytes and leukocytes count showed a significant (P<0.05) higher mean on the 2nd and 7th days of life compared to the other days (8.5×106 and 23×103/μl, respectively). Mean corpuscular volume (MCV), mean corpuscular haemoglobin (MCH) and mean corpuscular haemoglobin concentration (MCHC) changed significantly (P<0.05) with age. Differential leukocytes count was not affected significantly by the age. Neutrophilia was observed in neonate camels during the first week of life. Monocytes showed lower mean values in neonate camels during the first week of life compared to the adult camels. The obtained haematological values were compared to those reported by other investigators in young and adult camels, other animals and humans.